Diarrheal Diseases Hospitalization in Yemen before and after Rotavirus Vaccination - Mohammed Amood AL-Kamarany; Lina Al-Areqi; Abulatif Mujally; Fawzya Alkarshy; Arwa Nasser; Aisha O. Jumaan (Scientifica)
The study aims to assess the impact of rotavirus vaccine introduction on diarrheal diseases hospitalization and to identify the rotavirus genotypes most prevalent before and after vaccine introduction among children ≤ 5 years of age. Rotarix™ ® rotavirus vaccine is currently licensed for infants in Yemen and was introduced in 2012. The vaccination course consists of two doses. The first dose is administrated at 6 weeks of age and the second dose is completed by 10 weeks. Based on a longitudinal observational study, we assessed the impact of vaccination on rotavirus hospitalization before and after vaccination among children ≤ 5 years of age at the Yemeni-Swedish Hospital (YSH) in Taiz, Yemen. Prevaccination covered January 2009–July 2012 during which 2335 fecal samples were collected from children ≤ 5 years old. Postvaccination covered January 2013–December 2014 during which 1114 fecal samples were collected. Rotavirus was detected by Enzyme Linkage Immunosorbent Assay (ELISA). The incidence of rotavirus hospitalization decreased from 43.79% in 2009 to 10.54% in 2014. Hospitalization due to rotavirus diarrhea was reduced by 75.93%. Vaccine coverage increased from 23% in 2012 to 72% in 2014. Also, the results showed that the most predominant genotypes in prevaccination period were G2P[4] (55.0%), followed by G1P[8] (15.0%), while in postvaccination period G1P[8] (31%) was the predominant genotype, followed by G9P[8] (27.5%). In conclusion, rotavirus vaccination in Yemen resulted in sharp reduction in diarrheal hospitalization. A successful rotavirus vaccination program in Yemen will rely upon efficient vaccine delivery systems and sustained vaccine efficacy against diverse and evolving rotavirus strains.